2019
DOI: 10.1002/jsfa.10154
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of emulsion stabilized by table egg‐yolk granules at different pH levels

Abstract: BACKGROUND: The egg yolk is complex, which makes it difficult to understand why mayonnaise can be stabilized into a high internal-phase emulsion. This study aimed to assess the possibility of developing oil-in-water emulsions through unmodified natural egg-yolk granules (EYGs) at various pH levels, to further understand the precise mechanism of mayonnaise. RESULTS: Egg-yolk granules were obtained from hen egg yolk by centrifugation. The sizes of the EYGs were characterized using dynamic light scattering (DLS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
(22 reference statements)
3
8
0
Order By: Relevance
“…Previous studies also found decreasing trend in particle size of emulsion stabilized by EYGs as the pH increased from 3.0 to 9.0 at NaCl ionic strength of 0.15 M [ 20 ]. In addition, among all gel-like emulsions, the particle size of the emulsion at pH 5.0 was the largest, which was similar to other researchers’ studies [ 15 ]. However, the decreasing trend of emulsion particle size as the pH value moved away from the isoelectric point (pH 5.0) was contrary to the study by other researchers [ 15 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies also found decreasing trend in particle size of emulsion stabilized by EYGs as the pH increased from 3.0 to 9.0 at NaCl ionic strength of 0.15 M [ 20 ]. In addition, among all gel-like emulsions, the particle size of the emulsion at pH 5.0 was the largest, which was similar to other researchers’ studies [ 15 ]. However, the decreasing trend of emulsion particle size as the pH value moved away from the isoelectric point (pH 5.0) was contrary to the study by other researchers [ 15 ].…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure 1 B, the isoelectric point of EYGs was close to 5.0. However, in the absence of NaCl salt ions, the isoelectric point of the EYGs was 4.0 instead of 5.0 [ 15 ]. Similarly, it had also been found that the isoelectric point of the EYGs was between 4.0 and 5.0 with the addition of 0.15 M NaCl in solution [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they found that with increasing oil content, the pH of mayonnaise increased especially when the oil phase volume fraction is ([ 0.5). In the study conducted by Wang et al (2020), authors found that by decreasing the pH of mayonnaise, its stability improved and creaming was not accrued. They mentioned that, one reason could be through increasing the oil droplets size with the pH enhancement.…”
Section: Salt and Acidulantmentioning
confidence: 99%
“…Recently, the U.S. Food and Drug Administration (FDA) stated to ban the utilization of PHOs in processed food [16]. To meet the new requirements, an effective alternative of PHOs which could mimic the rheology and sensory features of the PHOs are the new challenges for food scientists [17][18][19][20][21]. Oleogelation, which uses the three-phase emulsion system to physically fabricate the artificial butter-like product, is a promising way to meet the increasing demand for healthier food.…”
Section: Introductionmentioning
confidence: 99%